THE ROLE OF SELF-EFFICACY, ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Milenia, Tiara; Ie, Mei (Graduate Program of Universitas Tarumanagara, 2024)
Organizational citizenship behavior is a voluntary, selfless act carried out by an employee outside of his work responsibilities as a form of contribution that can increase the effectiveness of the company. The formation of organizational citizenship behavior can be influenced by various factors, such as self-efficacy, organizational commitment, and job satisfaction. The purpose of this study was to determine the effect of self-efficacy, organizational commitment, and job satisfaction on organizational citizenship behavior. The sampling technique in this study used a non-probability sampling method. The sample of this study were all employees at PT XYZ which is engaged in food and beverages and has 36 members. The data collection technique used a questionnaire. The results showed that self-efficacy has a positive and significant effect on organizational citizenship behavior, organizational commitment has a positive and significant effect on organizational citizenship behavior, and job satisfaction has a positive and significant effect on employee organizational citizenship behavior. Companies can improve organizational citizenship behavior through providing intensive training so that employees can master more efficient work methods and can develop skills relevant to work. This can increase the self-efficacy of its employees in carrying out their work. This is expected to increase organizational citizenship behavior.